A multi-centre, double-blind, placebo-controlled, randomised trial of combination methotrexate and gefitinib versus methotrexate alone to treat tubal ectopic pregnancies (GEM3): trial protocol - James May (Trials, 2018)
Abstract Background Tubal ectopic pregnancy (tEP) is the most common life-threatening condition in gynaecology. Treatment options include surgery and medical management. Stable women with tEPs with pre-treatment serum human chorionic gonadotrophin (hCG) levels < 1000 IU/L respond well to outpatient medical treatment with intramuscular methotrexate. However, tEPs with hCG > 1000 IU/L can take significant time to resolve with methotrexate and require multiple outpatient monitoring visits. In pre-clinical studies, we found that tEP implantation sites express high levels of epidermal growth factor receptor. In early-phase trials, we found that combination therapy with gefitinib, an orally active epidermal growth factor receptor antagonist, and methotrexate resolved tEPs without the need for surgery in over 70% of cases, did not cause significant toxicities, and was well tolerated. We describe the protocol of a randomised trial to assess the efficacy of combination gefitinib and methotrexate, versus methotrexate alone, in reducing the need for surgical intervention for tEPs. Methods and analysis We propose to undertake a multi-centre, double-blind, placebo-controlled, randomised trial (around 70 sites across the UK) and recruit 328 women with tEPs (with pre-treatment serum hCG of 1000–5000 IU/L). Women will be randomised in a 1:1 ratio by a secure online system to receive a single dose of intramuscular methotrexate (50 mg/m2) and either oral gefitinib or matched placebo (250 mg) daily for 7 days. Participants and healthcare providers will remain blinded to treatment allocation throughout the trial. The primary outcome is the need for surgical intervention for tEP. Secondary outcomes are the need for further methotrexate treatment, time to resolution of the tEP (serum hCG ≤ 15 IU/L), number of hospital visits associated with treatment (until resolution or scheduled/emergency surgery), and the return of menses by 3 months after resolution. We will also assess adverse events and reactions until day of resolution or surgery, and participant-reported acceptability at 3 months. Discussion A medical intervention that reduces the need for surgery and resolves tEP faster would be a favourable treatment alternative. If effective, we believe that gefitinib and methotrexate could become standard care for stable tEPs. Trial registration ISRCTN Registry ISRCTN67795930. Registered 15 September 2016.